MENGGAGAS PENDIDIKAN KEWARGANEGARAAN BERBANTUAN MEDIA PODCAST UNTUK PENGUATAN CIVIC COMPETENCE SISWA DISABILITAS NETRA - Nanggala, Agil; Fahmi, Rizal (PELITA JURNAL PENELITIAN DAN KARYA ILMIAH, 2023)
This study attempts to finalize the idea of civic education assisted by podcast media to strengthen the civic competence of blind students. This research is based on descriptive qualitative, because it is natural, participatory and in-depth. The results of the study are that the idea of civic education assisted by podcast media is able to strengthen the civic competence of blind students because the presentation of civic education material is realized verbally or in dialogue in line with the needs of blind students. The stages of civic education practice assisted by podcast media are, finalizing the theme, interactive dialogue, narrative evaluation and reflection, then overcoming the individual or medical model of disability and also the charity model of disability, then reflecting the social model of disability, then making civic education more inclusive and accommodating to disabilities.